Characterization of Ladakhi churpe enriched with apricot and spinach - Hussain, Anwar; Ahmad, Sheikh Rafi; Kanwar, Maheshwar Singh (Indian Journal of Dairy Science, 2022)
The aim of this study was to produce novel churpe-products with apricot and spinach supplementation. These products being rich in antioxidants along with good source of minerals, vitamins and other essential nutrients could have enormous potentials to guard against many human diseases. To the tribal people of Ladakh, these could overcome the deficiency of micronutrients caused due the shortage of fruits and vegetables during the winter season. The nomads of Changthang region of Ladakh could carry these products easily as nutritional supplements during their year round migration. Dried dairy products viz. churpe-balls and churpe-strips were developed with the incorporation of apricot powder into cottage cheese at different levels (05, 10, 15 and 20%) and spinach powder at levels (03, 06, 09 and 12%), respectively. Physico-chemical, antioxidant, colour, sensory and microbial attributes of the products were studied. The addition of apricot powder in balls resulted in significant (P < 0.05) increase in ash, hydrosoluble vitamins (thiamine, riboflavin and ascorbic acid), titratable acidity and antioxidant activity and decrease in protein, fat, minerals (calcium, magnesium and sodium) and pH. Incorporation of spinach powder in strips resulted in increase (P < 0.05) in ash, calcium, magnesium, hydrosoluble vitamins (thiamine, riboflavin and ascorbic acid), titratable acidity and antioxidant activity and decrease in protein, fat, sodium and pH. A non significant increase in moisture and lactose contents of both the value added products was also observed. L* and a* increased in both the products with the increase in level of supplementation (05 to 20% in case of balls and 03 to 12% in case of strips), however, b* decreased in balls and increased in strips. Rise in the supplementation levels resulted in decline in microbial load in the products whereas, with the advancement of storage period up to 120 days, there was rise in microbial population but was found within safe limits. The overall acceptability of the churpe-balls was highest at 15% level and that of churpe-strips was highest at 09% level of blending.